Bion in Italia. Una nota storica - Iacarella, Andreas (Il sogno della farfalla, 2024)
The aim of this note is to briefly retrace the initial stages of Bion’s theoretical penetration into Italian psychoanalysis. It specifically highlights the role played by the figure of Francesco Corrao, SPI president between 1969 and 1974, and the book collection Serie di psicoanalisi (Armando publishing house). The author mentions some of the reasons at the root of this fortune, particularly in relation to Bionian theories of unconscious phenomena in the group dimension. Compared to these propositions, historically contextualized in the season of youth movements, it is possible to recognize a radical difference with the theory that Massimo Fagioli was proposing in those same years.